(untitled) (Experimental biology, 2025)
In plant cells exposed to stress, 18S rRNA has been observed to cleave as part of the small ribosomal subunit and accumulate a 135 nucleotide 5’-terminal fragment, termed 5,3S rRNA. However, the physiological significance of this phenomenon remains unknown. The aim of this study was to investigate the role of discrete 18S rRNA fragmentation in plants using the yeast toxin PiORF4, which can induce a similar cleavage in yeast. In this work, a mutated cDNA gene encoding a form of the PiORF4(E9D) toxin with increased specificity for 18S rRNA was generated. The mutated gene was cloned into the pET23c vector, followed by expression in Escherichia coli BL21(DE3) cells. The resulting recombinant PiORF4(E9D)-6His protein was successfully purified by metal ion affinity chromatography and its identification confirmed by immunoblotting. In addition, preliminary in vitro studies demonstrated the ability of PiORF4(E9D) to specifically target 18S rRNA under controlled conditions,